(NvIZNX aRSENXEWA(B: [(NrOMAN(B]; s (NpOWESTI I RASSKAZY (B/ s - (NbUNIN(B, (NiWAN aLEKSEEWI^s ((NmOSKWA(B: s (NpRAWDA(B, s, 1989)
(Nw SBORNIK RUSSKOGO PISATELQ i(B. (Na(B. (NbUNINA (B(1870 - 1953) (NWKL@^ENY ROMAN (B"(NvIZNX aRSENXEWA(B", (NA TAKVE POWESTI I RASSKAZY(B.s
rus
Keywords: (NaWTOBIOGRAFI^ESKIJ ROMANs; (NpOWESTXs